Association between Menopausal Symptoms and Overactive Bladder: A Cross-Sectional Questionnaire Survey in China - Zhu, Lingping; Cheng, Xiaoxia; Sun, Jiaxin; Lv, Shiyi; Mei, Suzhen; Chen, Xing; Xi, Sisi; Zhang, Jin; Yang, Mukun; Bai, Wenpei; Yan, Xiaoyan (PloS one, 2015)
The association between menopause and overactive bladder is controversial. The purpose of this study was to determine the association between menopausal symptoms and overactive bladder, and identify the risk factors for overactive bladder. A cross-sectional study was performed. The study included 403 women aged 36-76 years who visited the menopause clinic at Peking University First Hospital between September 2012 and December 2013. The overactive bladder symptom score and modified Kupperman index questionnaires were used. Differences were assessed using descriptive statistics to determine any association between the overactive bladder symptom score and modified Kupperman index score, and to evaluate the risk factors for overactive bladder. A total of 304 women were finally enrolled. The prevalence of overactive bladder was 9.43%, and the modified Kupperman index score; number of sexual problems; and frequency of urinary tract infections, vertigo, melancholia, and mood swings were significantly higher in patients with overactive bladder than in the patients without overactive bladder (p < 0.05). Menopausal symptoms (modified Kupperman index score ≥ 15) (odds ratio: 1.049, 95% confidence interval: 1.006-1.095, p = 0.025) and a low frequency of sexual intercourse in the last 6 months (odds ratio: 2.580, 95% confidence interval: 1.228-5.422, p = 0.012) were identified as independent risk factors for overactive bladder. The frequency of sexual intercourse was found to decrease with an increase in the severity of overactive bladder (p = 0.004, linear-by-linear association = 0.001). Menopausal symptoms may be closely associated with overactive bladder, and sexual activity may be associated with the severity of overactive bladder. Moreover, sexual problems, urinary tract infections, vertigo, melancholia, and mood swings may be associated with overactive bladder.